Crafting Culture in Early Childhood: Integrating Paper Cutting as an Intangible Cultural Heritage into Educational Curricula for Artistic Enrichment and Innovation - Has, tana (Pacific International Journal, 2024)
This study investigates the integration of paper cutting, a Chinese intangible cultural heritage, into early childhood education curricula, exploring its multifaceted impact on educational enrichment and the development of children's artistic literacy and innovative abilities. Against the backdrop of China's efforts to safeguard intangible cultural heritage, the research delves into effective strategies and methods for seamlessly embedding paper cutting into early childhood education. The comprehensive literature review traces the historical roots, global influence, cultural significance, and contemporary practices of paper cutting, providing a robust foundation for the analysis. The study emphasizes the role of teachers in instilling appreciation for paper cutting and contends that this traditional art form not only enhances children's creativity but also fosters teamwork and communication skills. Proposing the development of a structured teaching syllabus, an optimal teaching environment, and diverse practical activities, the research advocates for the integration of local cultural characteristics, contributing valuable insights to early childhood education and cultural heritage preservation.